A comparison of waste education in schools and colleges across five European cities. Issue 4 (19th May 2022) - Lee, Sheryl A.; Mork, Jane; Voća, Neven; Voronova, Viktoria; Virsta, Ana; Daraban, Ana E.; Pohlmann, Jennifer; Leal Filho, Walter; Ribić, Bojan; Banks, Craig E.
ABSTRACT: The European Union produces over 200 million tonnes of municipal waste each year with 47% being recycled or composted. With the EU reuse and recycling targets set at 55% by 2025 and the introduction of the EU's Circular Economy Action Plan there has never been more importance placed on waste and recycling education. A three-year transnational project 'An Erasmus+ Waste Education Initiative' set out to investigate the level of waste and recycling education (WE) that is currently being delivered in five European cities with a view to develop a range of materials to be used in the classroom extracting the best practice from each. This paper highlights the responses from a questionnaire sent to schools and colleges to determine the baseline of WE currently being delivered in Bucharest, Hamburg, Manchester, Tallinn and Zagreb. Factors such as the local waste and recycling infrastructure and population density were also considered to determine the extent of their influence on the type and availability of WE in the classroom. The findings indicate a wide variation in the amount of WE currently being delivered in the five cities. Increased recycling rates and level of infrastructure have an inverse effect on the level of teacher engagement and involvement in waste management projects does not have an impact on the amount of WE that is present in the curriculum or number of registered Eco-Schools. Time constraints due to other curriculum topics, awareness and lack of resources were the main reasons for not including WE in the classroom.